Methods for detection of drug resistance in trypanosomes - new developments? - Peregrine, A.S.; Wells, C.W.; Wilkes, J.M. (European Union, 2000)
Characterising the drug susceptibility of trypanosomes that are pathogenic for domestic livestock has for many years been carried out either in vivo, using large or small animals, or by using various in vitro cultivation methodologies (Peregrine, 1994). Thus, adaptation to, and multiplication of field isolates in, an experimental environment is often a requirement for obtaining drug sensitivity data. However, many in vivo and in vitro systems suffer from a number of shortcomings: (a) field isolates of trypanosomes frequently fail to establish or grow poorly, (b) it can often take many weeks or months to characterise a trypanosome population, and (c) it is generally not practical to screen a large number of trypanosome populations. As a result, for epidemiology studies, there is a need to develop new techniques that will rapidly characterise the drug sensitivity of large numbers of trypanosome isolates, immediately upon collection from domestic livestock. This review summarises three recent areas of research on resistance to isometamidium (SamorinÆ, Trypamidium) in trypanosomes and indicates whether or not the results may lead to the Development of such diagnostic tests.